Scopoletin 8-Hydroxylase-Mediated Fraxetin Production Is Crucial for Iron Mobilization. Issue 1 (20th March 2018) - Tsai, Huei-Hsuan; Rodríguez-Celma, Jorge; Lan, Ping; Wu, Yu-Ching; Vélez-Bermúdez, Isabel Cristina; Schmidt, Wolfgang
Abstract : In Arabidopsis thaliana, scopoletin 8-hydroxylase mediates the final step in the biosynthesis of fraxetin, a coumarin with a catechol moiety, which is secreted by roots of iron-deficient plants at elevated pH to mobilize iron. Abstract: Iron (Fe) is an essential mineral nutrient and an important factor for the composition of natural plant communities. Low Fe availability in aerated soils with neutral or alkaline pH has led to the evolution of elaborate mechanisms that extract Fe from the soil solution. In Arabidopsis ( Arabidopsis thaliana ), Fe is acquired by an orchestrated strategy that comprises mobilization, chelation, and reduction of Fe 3+ prior to its uptake. Here, we show that At3g12900, previously annotated as scopoletin 8-hydroxylase (S8H), participates in Fe acquisition by mediating the biosynthesis of fraxetin (7, 8-dihydroxy-6-methoxycoumarin), a coumarin derived from the scopoletin pathway. S8H is highly induced in roots of Fe-deficient plants both at the transcript and protein levels. Mutants defective in the expression of S8H showed increased sensitivity to growth on pH 7.0 media supplemented with an immobile source of Fe and reduced secretion of fraxetin. Transgenic lines overexpressing S8H exhibited an opposite phenotype. Homozygous s8h mutants grown on media with immobilized Fe accumulated significantly more scopolin, the storage form of scopoletin, supporting the designated function of S8H in scopoletin hydroxylation. Fraxetin exhibited Fe-reducing properties in vitro with higher rates being observed at neutral relative to acidic pH. Supplementing the media containing immobile Fe with fraxetin partially rescued the s8h mutants. In natural Arabidopsis accessions differing in their performance on media containing immobilized Fe, the amount of secreted fraxetin was highly correlated with growth and Fe and chlorophyll content, indicating that fraxetin secretion is a decisive factor for calcicole-calcifuge behavior (i.e. the ability/inability to thrive on alkaline soils) of plants.